Does competition enhance performance or cheating?: a laboratory experiment - Schwieren, Christiane; Weichselbaumer, Doris (Journal of economic psychology, 2010)
In this paper, we experimentally test whether competing for a desired reward does not only affect individuals’ performance, but also their tendency to cheat. Recent doping scandals in sports as well as forgery and plagiarism scandals in academia have been partially explained by “competitive pressures”, which suggests a link between competition and cheating. In our experiment subjects conduct a task where they have the possibility to make use of illegitimate tools to better their results. ...
Online veröffentlicht am 8. April 2009
Gesehen am 11.07.2023